Riluzole, a Derivative of Benzothiazole as a Potential Anti-Amoebic Agent against Entamoeba histolytica - Maritza Velásquez-Torres; José Guadalupe Trujillo-Ferrara; Marycarmen Godínez-Victoria; Rosa Adriana Jarillo-Luna; Víctor Tsutsumi; Virginia Sánchez-Monroy; Araceli Posadas-Mondragón; Roberto Issac Cuevas-Hernández; José Angel Santiago-Cruz; Judith Pacheco-Yépez (MDPI AG, 2023)
Amoebiasis is produced by the parasite Entamoeba histolytica; this disease affects millions of people throughout the world who may suffer from amoebic colitis or amoebic liver abscess. Metronidazole is used to treat this protozoan, but it causes important adverse effects that limit its use. Studies have shown that riluzole has demonstrated activity against some parasites. Thus, the present study aimed, for the first time, to demonstrate the in vitro and in silico anti-amoebic activity of riluzole. In vitro, the results of Entamoeba histolytica trophozoites treated with IC50 (319.5 μM) of riluzole for 5 h showed (i) a decrease of 48.1% in amoeba viability, (ii) ultrastructural changes such as a loss of plasma membrane continuity and alterations in the nuclei followed by lysis, (iii) apoptosis-like cell death, (iv) the triggering of the production of reactive oxygen species and nitric oxide, and (v) the downregulation of amoebic antioxidant enzyme gene expression. Interestingly, docking studies have indicated that riluzole presented a higher affinity than metronidazole for the antioxidant enzymes thioredoxin, thioredoxin reductase, rubrerythrin, and peroxiredoxin of Entamoeba histolytica, which are considered as possible candidates of molecular targets. Our results suggest that riluzole could be an alternative treatment against Entamoeba histolytica. Future studies should be conducted to analyze the in vivo riluzole anti-amoebic effect on the resolution of amebic liver abscess in a susceptible model, as this will contribute to developing new therapeutic agents with anti-amoebic activity.